PERANAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA - ARIANTI, ARIANTI (DIDAKTIKA, 2018)
The role of teachers in improving student learning motivation is one of the integral activities that must be in learning activities. In addition to providing and transferring teacher knowledge is also tasked to improve children's motivation in learning. It cannot be denied that student learning with others is very different, that's why it is important for teachers to always motivate students so that students always have the spirit of learning and being able become students who excel and can develop themselves optimally. The learning process will succeed if students have motivation in learning. Therefore, teachers need to foster optimal student motivation. Teachers are demanded to be creative to arouse student learning motivation. Learning motivation is meaningfulness, value, and the benefits of learning learning activities are quite interesting for students to do learning activities.